2007
DOI: 10.1093/ajcn/86.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Role of S-adenosylmethionine, folate, and betaine in the treatment of alcoholic liver disease: summary of a symposium

Abstract: This report is a summary of a symposium on the role of S-adenosylmethionine (SAM), betaine, and folate in the treatment of alcoholic liver disease (ALD), which was organized by the National Institute on Alcohol Abuse and Alcoholism in collaboration with the Office of Dietary Supplements and the National Center for Complementary and Alternative Medicine of the National Institutes of Health (Bethesda, MD) and held on 3 October 2005. SAM supplementation may attenuate ALD by decreasing oxidative stress through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
165
0
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(180 citation statements)
references
References 79 publications
5
165
0
9
Order By: Relevance
“…For example, Kwon et al recently showed that betaine supplementation in mice inhibited hepatic fat accumulation and prevented the decrease in antioxidant capacity against free radicals induced by a high fat diet [39]. Choline metabolism intermediates SAM and betaine have also been shown to reduce pro-inflammatory cytokines such as tumour necrosis factor-a (TNF-a) and to inhibit apoptosis of hepatocytes in animals [40,41]. One hypothesis regarding this property of betaine is that it contains an electrophilic methyl group that may prevent and/or reduce reductive and oxidative stress [40].…”
Section: Animal Studiesmentioning
confidence: 99%
“…For example, Kwon et al recently showed that betaine supplementation in mice inhibited hepatic fat accumulation and prevented the decrease in antioxidant capacity against free radicals induced by a high fat diet [39]. Choline metabolism intermediates SAM and betaine have also been shown to reduce pro-inflammatory cytokines such as tumour necrosis factor-a (TNF-a) and to inhibit apoptosis of hepatocytes in animals [40,41]. One hypothesis regarding this property of betaine is that it contains an electrophilic methyl group that may prevent and/or reduce reductive and oxidative stress [40].…”
Section: Animal Studiesmentioning
confidence: 99%
“…SAM effect was largely studied in liver disease, also with attention to its antioxidant properties [9,[91][92]. SAM led to inhibition of liver lipid peroxidation in a rat model of acute biliary obstruction and reduced mitochondrial oxidative stress in a rat model of liver ischemia/reperfusion [93].…”
Section: Involvement Of Sam In Oxidative Stress and Neurodegenerationmentioning
confidence: 99%
“…Increasing evidence suggests that altered methionine/folate metabolism may contribute to the development of hepatic injury. Folate deficiency may accelerate or promote hepatic injury by increasing hepatic homocysteine and S-adenosylhomocysteine concentrations decreasing hepatic S-adenosylmethionine and glutathione concentrations increasing lipid peroxidation and decreasing global DNA methylation (Purohit et al, 2007). Hyperhomocysteine also may promote insulin resistance (Björck et al, 2006;Li et al, 2008) and alter lipid metabolism (Liao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%